Partisipasi Masyarakat Lokal Dalam Pengelolaan Sampah Berbasis Sumber Mendukung Desa Wisata Berkelanjutan (Studi Kasus Desa Wisata Taro, Bali) - Kalpikawati, Ida Ayu; Pinaria, Ni Wayan Chintia (Jurnal Ilmiah Pariwisata, 2023)
Starting from the handling of waste at the village level that has not been maximized, waste from household activities is often thrown away by the community, causing environmental problems in Taro Village. The problem that is caused mainly occurs during the rainy season where many gots are blocked so that water overflows to the road body. Taro Village then invites the community to participate in managing the waste generated to maintain the cleanliness of the village environment by implementing source-based waste management. This study aims to determine the stages of participation, forms of participation and factors that influence community participation in waste management in Taro Village. This research uses a qualitative approach and research data is obtained through interviews, observations and documentation studies. The results showed that the stages of participation include the planning stages, implementation stages and utilization stages. The forms of participation are mind-bodied participation, energy participation, property participation, skills participation and social participation Factors that influence participation are internal factors, namely growing public awareness of the concept of source-based waste management and community behavior factors in implementing a clean culture. External factors that become reinforcement are the role of indigenous villages which are very effective and the obstacle is the lack of waste processing facilities at TPS 3 R. Keywords: Community Participation, Waste Management